(untitled) (LACCEI, 2024)
The general objective of the present investigation is to analyze the proposal of the reinforcement with jacketed concrete to protect the abutments of the bridges subjected to scour by the action of water during the occurrence of maximum floods in steep rivers, with invaded riverbeds and subject to recurring weather phenomena. This proposal was compared with the alternatives of maintaining the current protection, riprap, and concrete bag revetment. The analysis showed that the maximum scours depth is markedly different in the two abutments because the bridge is located on a curve. Considering the estimated scour in each abutment for a return period of 500 years, the height of the reinforcement was considered, resulting in a height of 5.50 m for the right abutment and 10.50 m for the left abutment. Technical analysis showed that the current protection is inadequate. concrete bag revetment does not meet the requirements either because the geotextile used in the bags does not resist the acting shear stress. Reinforced concrete jacketing and riprap lining meet the requirements, but liner costs up to 50% less than riprap lining. In addition, for construction reasons, the riprap alternative is ruled out since the riprap toe interferes with part of the area below the pillar closest to the abutment. In addition, it has been shown that the reinforcement with jacketed of concrete has the advantage of not occupying as much ground as the riprap.